Energy use and appliance ownership in Ireland - Eimear Leahy; Seán Lyons (The Economic and Social Research Institute (ESRI), 2009)
This paper examines domestic energy use and appliance ownership in Ireland. Regression analyses on a large micro-dataset reveal how household characteristics can help explain the ownership of energy using appliances. The location of the household, the number of rooms and household income are important factors, as are certain characteristics of the highest earner in the household such as education level and age. We also find evidence that household income, number of persons, accommodation characteristics, region, and age of the highest earner can help explain domestic electricity use, even after taking account of the household's endowment of appliances. The level of demand for domestic heating is also associated with housing tenure and the employment status of the highest earner.
Keywords: 330; energy use; Ireland; appliance ownership; energy efficiency; Privater Haushalt; Elektrohaushaltsgerät; Energiekonsum; Haushaltseinkommen; Irland